A Closer Look on the Main Characters Tendency: BUMI MANUSIA by Pramoedya Ananta Toer - Gari, Nelia; Herdi, Herdi; Agus, Ichsan J.M. H. T.; Putri, Wella C.; Pradina, Siska (International Journal for Educational and Vocational Studies, 2019)
A novel is a story that is related to real or fictional events imagined by the author through their observation of reality. The analysis of this present article aims to describe the magnitude of the characterization effect through a character figure and the position of the characters in the novel "Bumi Manusia" by Pramoedya Ananta Toer. The method used in this research is character description to explain individual characteristics tendency and the condition of a group more accurately, particularly the characters called Minke, Annelies, and Nyai Ontosoroh; the three most prominent figures. As the lead character, Minke fights against injustice; readers realize a most valuable lesson, seen in page 12, which says, My personality becomes more different from my countrymen in general, violating my form as a Javanese person.